Morocco overview - Aderghal, M. (University of London, 2023)
Morocco is included in the African and Euro-Mediterranean mobility space. There has been internal and international migration for generations. Migration trajectories are complex and have varied during different phases of the country’s history. Traditional migrations have been movements of mainly internal pastoral populations and commercial exchanges and pilgrimages. More recent migrations are driven by the search for work and better living conditions. Emigration for work from the countryside to the cities and abroad is a result of integrating the country’s economy into global market chains initiated at the end of the 19th century by colonial companies exploiting agricultural land, forests, and mineral resources. Independence in 1956 was followed by an extension of the labor market, an increase in the intensity of migration from the countryside to and between the cities, and a widening of access by rural and urban households to modern consumer goods. International emigration from Morocco was stimulated in the 1960s by the European demand for labor and was a factor in policies for economic growth.